DYNAMICS OF CONSTITUTION IN 1945 AMENDMENTS AS A CONSTITUTIONAL IN INDONESIA - Asri Agustiwi (UNTAG Law Review, 2017)
The constitution is often equated with the Constitution as the basic law is written. However, the Constitution of having understanding wider. The Constitution does not only include a written rule that constitution, but the unwritten rule, the basic rules are raised and maintained in the practice of statecraft or called by convention. The Constitution is the constitutional system in the form of written and unwritten rules set out together to govern a country. Where the nature and function of the constitution is there limitation of government power so that the implementation of power is not arbitrary. Thus, the rights of citizens are expected to be protected. 1945 was passed by the state constitution PPKI as Indonesia on August 18, 1945. In practice, the 1945 Constitution of Indonesia has been transformed into constitutional RIS (December 27th 1945- August 17, 1950), later transformed into a Provisional Constitution of 1950 (August 17th 1950s July 5th, 1959), until it became 1945 again but with amendments in 1999, 2000, 2001 and 2002. An amendment to the 1945 Constitution because their demands strong 1945 changes of society. People feel that the charge 1945 times many are not appropriate.